Apreciação do povoamento do neolítico inicial na Baixa Bacia do Douro: A Lavra I (Serra da Aboboreira) como caso de estudo - Sanches, Maria de Jesus (2020)
This text is devoted to the discussion of the archaeographic documentation of the Early Neolithic archaeological site of Lavra I (Serra da Aboboreira; Aboboreira Mountain), bringing into focus the phenomena of sedimentation and formation of the archaeological record, the type of occupation and the explanation of the C14 dates. It also discusses how Lavra I is inscribed at the beginning of the neolithicization process in the North of Portugal and the Lower Douro basin, highlighting, in Serra da Aboboreira, the possibility of a temporal and spatial relationship with the oldest barrows (mamoas), in the 2nd quarter of the 5th mil. B.C.